Effects of varied packages of plyometric training on selected motor ability components among university students - Wasim Khan; Tasleem Arif; Khushdil K. Muhammad; Sardar N. Sohail; Irina V. Kriventsova (Physical Education of Students, 2020)
Background and Study Aim. The main focus of the study was to examine the effect of varied packages of plyometric training on speed, leg explosive power, and muscular endurance among university students.